Atribut Yang Menjadi Pertimbangan Konsumen Dalam Membeli Produk Perumahan : Penelitian dan Analisis Conjoint - Tambunan, Damelina B. (Universitas Prasetiya Mulya, 2009)
The very high competitiveness of business nowadays, encourages the marketers to focus on satisfying their customers. Therefore marketers should be able to meet the customers’ demands. Customers usually consider a bundle of benefit before deciding to purchase products; therefore, marketers also should be able to identify the customers’ consideration of some product attributes. The aim of this study is to identify the combination of attributes that is considered by customers in making decision when purchasing property. The Data in this research are primary data and gathered from 150 respondents. The sampling method used is convenience sampling. The data are analyzed by using conjoint analysis. The result shows that the most considered attributes are the number of bed rooms, the size of land, the housing types, the house design, and the number of bath rooms.